Some Relations Between the Sets of f-Statistically Convergent Sequences - Colak, Rifat (Springer International Publishing Ag, 2020)
In this study we first established the relations between f-density and g-density of a subset of the set of positive integers for any modulus functions f and g. Using the obtained facts we establish the relationship between the sets S-f and S-g of statistically convergent and BSf and BSg of statistically bounded sequences which defined by modulus functions f and g.
4th International Conference on Computational Mathematics and Engineering Sciences (CMES) -- APR 20-22, 2019 -- Akdeniz Univ, Antalya, TURKEY
Keywords: Density; Modulus function; Statistical convergence; Statistical boundedness